GREEN PERCEIVED VALUE ON GREEN PRODUCT AWARENESS AND GREEN SATISFACTION MODERATED BY GENDER - Conny Tjandra Rahardja; Da’isya Arumanda Chitta Fataya (LPPM STIE YKPN Yogyakarta, 2023)
The interest in this research arises from the contradiction between the increasing need for tissue use in modern society based on data from the Food and Agriculture Organization (FAO) and the threat it poses to environmental sustainability through deforestation for tissue raw materials and tissue waste disposal. One of the companies that actively promotes the production of environmentally friendly tissue is Tessa tissue manufacturer. This research utilizes purposive sampling technique, selecting members of the green community who consume various Tessa tissue products. The data processing in this study employs the PLS-SEM method using SmartPLS 3 software. The research includes measurement model testing, structural model testing, hypothesis testing, and moderation testing. The results of the study indicate that green perceived value has a positive effect on green awareness and green satisfaction. Gender does not moderate the influence of green perceived value on green awareness and green satisfaction.